Modification of Microcontroller-Based Batik Canting as A Temperature and Viscosity Control of Night Wax - Cika Faradila; Sulandari Sulandari; Hilyati Iftinan Lubis; Rangga Prasetyo Darmawan; Sigit Irawan; Rita Juliani (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2022)
The leakage of the wax during the casting of the candle using conventional canting hampers the process of making batik, especially coloring, thereby damaging the motif and reducing the quality of written batik. The solution given is related to the problem of leakage of night wax through E-Canting which is modified from conventional canting using an Arduino nano microcontroller, connected to a temperature sensor, heater plate, and servo to facilitate batik craftsmen in waxing. The use of a microcontroller connected to a temperature sensor to maintain a stable temperature and viscosity of the night wax with the process of releasing the wax is regulated using a lever system that is connected via a servo. The manufacture of E-Canting is carried out in three stages, namely coding through Arduino IDE (Integrated Development Environment) software, assembling components using solder by connecting Arduino nano to other electronic components such as temperature sensors, heater plates, servos, LCDs, and incorporating the E-Canting framework. and electronic components. The energy used by the E-Canting is in the form of electricity which is channeled through the battery so that batik craftsmen can use the E-Canting as needed. The use of E-Canting is able to stabilize the temperature and viscosity of the night wax so as to minimize the occurrence of leakage. E-Canting is able to melt night wax with the required viscosity of 5.54 Pa at 80° in 3.39 minutes which has the potential to increase the amount of quality batik production.